2003
DOI: 10.1111/1540-5885.310001-i1
|View full text |Cite
|
Sign up to set email alerts
|

Mutuality as background music in women's lived experience of mental health and depression

Abstract: Mental health problems, especially depression, have turned into an extensive public health problem, affecting women in particular. The aim of this study was to obtain a deeper understanding of mental health phenomena through elderly women's lived experiences of mental health and depression. The phenomenological approach was chosen for collecting experience-based and person-centred descriptions from 21 women, focusing on mental health and depression. The interviews were analysed using Giorgi's phenomenological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 25 publications
(29 reference statements)
0
52
0
1
Order By: Relevance
“…Eight studies were conducted in the USA (Ugarriza, 2002;Pierce et al, 2003;Barg et al, 2006;Soonthrochaiya & Dancy 2006;Black et al, 2007;Switzer et al, 2009;Wittink et al, 2009;Conner et al, 2010), one in the UK (Lawrence et al, 2006), three in Sweden (Hedelin & Strandmark, 2001a;Hedelin & Strandmark, 2001b;Hedelin & Jonsson, 2003) and one in New Zealand (Allan & Dixon, 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were conducted in the USA (Ugarriza, 2002;Pierce et al, 2003;Barg et al, 2006;Soonthrochaiya & Dancy 2006;Black et al, 2007;Switzer et al, 2009;Wittink et al, 2009;Conner et al, 2010), one in the UK (Lawrence et al, 2006), three in Sweden (Hedelin & Strandmark, 2001a;Hedelin & Strandmark, 2001b;Hedelin & Jonsson, 2003) and one in New Zealand (Allan & Dixon, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Three studies employed a phenomenological approach (Hedeling & Strandmark, 2001a;Hedelin & Strandmark, 2001b;Hedelin & Jonsson, 2003), while another used cultural consensus analysis . Two studies employed content analysis (Ugarriza, 2002;Conner et al, 2010), two studies qualitative content analysis (Soonthorchaiya & Cancy, 2006;Black et al 2007), while a further two applied grounded theory (Lawrence et al, 2006;Wittink et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…power, knowledge, beliefs and values, experience, attitudes) and not easy to achieve. However, mutuality was experienced as a form of background music related to mental health and depression (Hedelin & Jonsson, 2003).…”
Section: Depression and Self-management Discussionmentioning
confidence: 99%
“…Themes of negative memories, failures and catastrophic views of the present and future were prevalent. Hedelin and Jonsson (2003) similarly used a phenomenological approach to collect experience-based and person-centered descriptions of depression from 21 elderly women. They found that the women's experiences of mental health or depression were heavily influenced by their sense of value and self-esteem in relation to themselves and others.…”
Section: ! ! 4!mentioning
confidence: 99%